rptA, a novel gene from Ensifer (Sinorhizobium) meliloti involved in conjugal transfer - Pistorio, Mariano (2013)
We approached the identification of Ensifer (Sinorhizobium) meliloti conjugal functions by random Tn5-B13 mutagenesis of the pSmeLPU88a plasmid of E. meliloti strain LPU88 and the subsequent selection of those mutants that had lost the ability to mobilize the small plasmid pSmeLPU88b. The Tn5-B13-insertion site of one of the mutants was cloned as an EcoRI-restricted DNA fragment that after subsequent isolation and sequencing demonstrated that a small open reading frame of 522 bp (designated rptA, for rhizobium plasmid transfer A) had been disrupted. The predicted gene product encoded by the rptA sequence shows a significant similarity to two hypothetical proteins of the plasmid pSmed03 of Ensifer medicae WSM419 and other rhizobia plasmids. No significant similarity was found to any protein sequence of known function registered in the databases. Although the rptA gene was required for pSmeLPU88b-plasmid mobilization in the strain 2011 background, it was not required in the original strain LPU88 background.